1980
DOI: 10.3133/pp1116
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical-exploration studies in the Coeur d'Alene district, Idaho and Montana

Abstract: The principal ore deposits in the Coeur d'Alene district are leadzinc-silver replacement veins in Precambrian rocks of the Belt Supergroup. The main ore minerals are galena, tetrahedrite, and sphalerite. The host rocks are mainly quartzite, siltite, and argillite. Cretaceous quartz monzonite locally intrudes the Belt rocks.The geochemical investigations reported here were carried out to determine if geochemical methods would be useful in the search for concealed ore deposits. About 8,700 soil samples and 4,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…10) suggest that 20 to 30 percent of the lead is from the crustal endmember. Using average lead contents of Proterozoic Belt rocks and subduction-related andesite of about 15 to 20 ppm (Harrison and Grimes, 1970;Gott and Cathrall, 1980) and 6 ppm (Gill, 1981), respectively, we infer the plutons could represent "normal" subduction-related melts contaminated by roughly 5 to 15 wt % Proterozoic rock.…”
Section: Crystallization Environment and General Originsupporting
confidence: 55%
“…10) suggest that 20 to 30 percent of the lead is from the crustal endmember. Using average lead contents of Proterozoic Belt rocks and subduction-related andesite of about 15 to 20 ppm (Harrison and Grimes, 1970;Gott and Cathrall, 1980) and 6 ppm (Gill, 1981), respectively, we infer the plutons could represent "normal" subduction-related melts contaminated by roughly 5 to 15 wt % Proterozoic rock.…”
Section: Crystallization Environment and General Originsupporting
confidence: 55%
“…), isotopic evidence that the Pb in stibnite was derived from Belt rocks, and the restricted occurrence of stibnite veins in the Prichard Formation, we surmise that the Sb in the stibnite veins also was derived from the Prichard Formation. Previous geochemical analyses of soil and rock in the Coeur d'Alene district (Gott & Cathrall ) and stream sediment in the Wallace 1 × 2° quadrangle (Leach & Hopkins ) have shown that the background abundance of Sb in the Prichard is about 1 ppm. Together with knowledge of the concentration of Sb in ore fluids (2000 ppm), the amount of Sb in the US Antimony mine (15.4 kt) and the respective densities of the Prichard Formation and hydrothermal fluids (approximately 2.65 and 1 g/cc), it is possible to estimate the minimum volumes of source rock (assuming 100% recovery of Sb) and ore fluid required to generate the deposit.…”
Section: Resultsmentioning
confidence: 99%
“…Health problems in the basin for humans and wildlife are linked to high concentrations of particulate Pb in surface soils and sediment and to ingestion of those particles. Elevated concentrations of particulate Pb are associated with soils that formed over mineralized rocks in the area (Gott and Cathrall, 1980), tailings from mills that processed the mineralized rock (Long, 1998b), and atmospheric fallout from smelters that operated in the mining district (U.S. Environmental Protection Agency, 1994). There are no new sources of particulate Pb from smelters or tailings today be-cause of closure of the smelters and environmental regulations that prohibit the dumping of tailings into rivers.…”
Section: Particulate Leadmentioning
confidence: 99%